Actors and Practices: An Institutional Study on Management Accounting Change in Air Greenland - Lars Balslev (Copenhagen Business School (CBS), 2017)
Actors and practices – An institutional study on management accounting change in Air Greenland My former CEO was one of the first executives in Greenland to formally implement an extensive commercial strategy to identify the contradictory forces of social obligations and commercial strivings. This strategy was aimed at connecting managers, executives, and directors under a vision that was calibrated commercially and sociopolitically in support of a commercial airline that was a state-owned enterprise (SOE). In one of my first interviews with my CEO, I asked him about managing an SOE with a strong societal obligation. He noted that: “…there is some inherent conflict in having the type of ownership we have, one in which the commercial owner demands higher profits or they will sell their shares, and the other two government owners, where one wishes to have the lowest possible fares and better infrastructure and the other one just wants less trouble. Well! This is the ongoing inherent conflict of the owner composition we just have to deal with.” He emphasized that SAS, the more “commercial oriented” owner and private shareholder, wanted higher profits and gains, whereas the Government of Greenland, the “social oriented” owner, wanted their SOE to deliver affordable tickets and better infrastructure at a lower price. The Danish government was stuck in the middle of these conflicting forces, because they could see the validity of both the commercial and the social aspects. He emphasized that operating an organization that followed a social, political, and economic track made it difficult to determine the development of the organization. He saw that managers who adhered to following these tracks simultaneously created a wider range of rationalities in terms of socioeconomic output.
hdl:10398/9501
Keywords: 650